Mine grouting reinforcement material
Patent Information
- Application Number
- CN202611443997.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
然而,该方案在实际应用于矿山破碎围岩注浆加固时仍存在以下不足:(1)纳米二氧化硅掺量较高(5~10份),高掺量纳米颗粒易发生团聚效应,反而劣化浆液的流动性和分散性,且增加了材料成本;(2)该方案未添加缓凝剂,浆液凝结时间不可调控,在矿山长距离泵送或大范围注浆施工中,浆液过早凝结易导致堵管事故,影响施工连续性;(3)该方案未添加膨胀剂,水泥基材料硬化过程中的化学收缩和干燥收缩无法得到有效补偿,固结体易产生收缩开裂,降低注浆加固的长期耐久性;(4)其胶凝体系缺少矿渣微粉组分,后期强度发展和体积稳定性仍有提升空间
(1)本发明通过矿渣微粉、粉煤灰和硅灰的复合掺入,优化了胶凝材料的颗粒级配,改善了浆液的稳定性和固结体的密实性。
Smart Images

Figure CN123003228A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic materials technology, and in particular to a grouting reinforcement material for mines. Background Technology
[0002] During mining operations, factors such as mining activity, changes in geological structure, and redistribution of stress in the surrounding rock can easily lead to problems such as fissure propagation, spalling, roof falls, floor heave, and loosening and fracturing of the surrounding rock in roadways, goafs, fault fracture zones, and coal-rock fissure zones. Especially in deep mines, high-stress mines, and under conditions of fractured and weak surrounding rock, the poor stability of the surrounding rock and the significant development of fissures can easily cause support structure failure, exacerbated roadway deformation, and safety accidents. Therefore, timely and effective grouting reinforcement of fractured coal-rock masses and surrounding rock fissures is an important technical means to improve the overall strength and stability of the surrounding rock in mines and ensure safe production.
[0003] Grouting reinforcement materials are a key component of mine grouting reinforcement technology. Their fluidity, injectability, setting time, early strength, later strength, volume stability, and durability directly affect the grout diffusion range and the final reinforcement effect. Currently, commonly used mine grouting materials mainly include cement-based grouts, chemical grouts, and organic-inorganic composite grouts. Among them, cement-based grouting materials are widely used due to their wide availability of raw materials, low cost, and good durability. However, traditional cement grouts generally suffer from problems such as coarse particles, insufficient fluidity, poor penetration into small cracks, slow early strength development, bleeding and segregation, and shrinkage cracking of the solidified body, making it difficult to meet the requirements for rapid reinforcement of complex and fractured surrounding rock.
[0004] While chemical grouts offer advantages such as low viscosity, good permeability, and rapid setting, some chemical grouts suffer from drawbacks including high cost, insufficient environmental friendliness, difficulty in controlling the reaction process, and poor durability, limiting their application in large-scale grouting reinforcement in underground mines. For example, Chinese invention patent CN121850502A discloses a grouting material for andesitic basalt formations, composed of 40-60 parts silicate cement clinker, 20-30 parts fly ash microspheres, 10-20 parts silica fume, 5-10 parts nano-silica, 0.5-1.5 parts polycarboxylate superplasticizer, 0.1-0.5 parts hydroxypropyl methylcellulose, and water. By compounding ultrafine fly ash microspheres, silica fume, and nano-silica and employing a high-speed shearing process, the aim is to reduce the grout particle size and improve its fluidity. However, when this scheme is actually applied to the grouting reinforcement of crushed surrounding rock in mines, the following shortcomings still exist: (1) The amount of nano-silica is relatively high (5-10 parts). High-volume nanoparticles are prone to agglomeration, which deteriorates the fluidity and dispersibility of the grout and increases the material cost; (2) No retarder is added to this scheme, so the grout setting time cannot be controlled. In long-distance pumping or large-scale grouting construction in mines, premature grout setting can easily lead to pipe blockage accidents and affect the continuity of construction; (3) No expansion agent is added to this scheme, so the chemical shrinkage and drying shrinkage during the hardening process of cement-based materials cannot be effectively compensated. The solidified body is prone to shrinkage cracking, which reduces the long-term durability of grouting reinforcement; (4) Its cementitious system lacks slag powder components, so there is still room for improvement in the later strength development and volume stability.
[0005] Therefore, in response to the problems of insufficient fluidity, poor injectability, low early strength, shrinkage cracking, and unstable reinforcement effect of existing mine grouting reinforcement materials, it is necessary to further study a composite cement-based grouting reinforcement material suitable for the reinforcement of fractured surrounding rock and fissures in mines. This material should possess good fluidity, pumpability, early strength, late strength, and volume stability, and be able to fully diffuse and rapidly consolidate in the fissures of fractured coal and rock masses, thereby improving the overall bearing capacity of the surrounding rock and reducing safety risks such as spalling, roof collapse, and roadway deformation. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the existing technology and to propose a grouting reinforcement material for mines.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A grouting reinforcement material for mines, wherein the cementitious components of the grouting reinforcement material include ordinary silicate cement, slag powder, fly ash, silica fume, and nano-silica; The slag powder comprises 20-30 parts by weight, and the nano-silica comprises 1-3 parts by weight.
[0008] Preferably, the ordinary silicate cement comprises 40-60 parts, fly ash comprises 10-20 parts, and silica fume comprises 5-15 parts.
[0009] Preferably, the slag powder is S95 grade slag powder, and the fly ash is secondary grade fly ash.
[0010] Preferably, the grouting reinforcement material further includes a polycarboxylate-based high-efficiency water-reducing agent, wherein the amount of the polycarboxylate-based high-efficiency water-reducing agent added is 0.2 to 0.5 parts by weight.
[0011] Preferably, the grouting reinforcement material further includes sodium gluconate, and the amount of sodium gluconate added is 0.1 to 0.3 parts by weight.
[0012] Preferably, the grouting reinforcement material further includes an expanding agent, and the amount of expanding agent added is 0.1 to 0.5 parts by weight.
[0013] Preferably, the expansive agent is a UEA-type low-alkali concrete expansive agent.
[0014] Preferably, the water-cement ratio of the grouting reinforcement material is 0.32.
[0015] A method for using the above-mentioned mine grouting reinforcement material includes the following steps: Step 1: Add ordinary silicate cement, slag powder, fly ash, silica fume and expansion agent to a mixing container and dry mix for 2-3 minutes; then add nano silica and continue to dry mix for 2-3 minutes to obtain a mixed dry powder. Step 2: Add polycarboxylate superplasticizer and sodium gluconate to water and stir until fully dissolved to obtain an aqueous solution of the additive; Step 3: Slowly add the aqueous solution of the additive to the mixed dry powder and stir until the slurry is uniform and there is no obvious agglomeration, thus obtaining the mine grouting reinforcement slurry.
[0016] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention optimizes the particle size distribution of cementitious materials by incorporating slag powder, fly ash and silica fume, thereby improving the stability of slurry and the compactness of solidified body.
[0017] (2) The present invention uses low-dosage nano-silica to modify cement-based materials, and utilizes its nucleation effect and pozzolanic activity to promote the hydration reaction of cementitious materials, which is beneficial to improving the early strength and later strength of the solidified body.
[0018] (3) The present invention improves the fluidity and dispersibility of grout by using polycarboxylic acid-based high-efficiency water-reducing agent, so that the grout still has good pumpability and injectability at a low water-cement ratio; by adjusting the setting time of grout by sodium gluconate, sufficient operable time is provided for long-distance pumping grouting in mines, avoiding the problem of pipe blockage caused by excessive setting; by compensating for the volume shrinkage of cement-based materials during the hardening process by using an expansion agent, it is beneficial to reduce the tendency of shrinkage cracking of the solidified body and improve the long-term stability of grouting reinforcement.
[0019] (4) The synergistic effect of the above components of the present invention enables the solidified body to have high compressive strength, good volume stability and compactness, which can meet the engineering requirements of grouting reinforcement of fractured surrounding rock and coal and rock fissures in mines. Attached Figure Description
[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 A comparison chart of the flowability of the grout in each embodiment and comparative example; Figure 2 A comparison chart of the slurry setting times for each embodiment and comparative example; Figure 3 Comparison diagrams showing the compressive strength of each embodiment and comparative example at different ages; Figure 4 A curve comparison of the effect of polycarboxylate superplasticizer dosage on the performance of grouting materials; Figure 5 A curve comparison of the effect of nano-silica content on the performance of grouting materials; Figure 6 A curve comparison of the effect of S95 grade slag powder content on the performance of grouting materials. Detailed Implementation
[0022] This embodiment provides a nano-modified composite cement-based grouting reinforcement material for mining. Its cementitious material is composed of ordinary silicate cement, slag powder, fly ash, silica fume and nano-silica. The admixtures include polycarboxylate-based high-efficiency water-reducing agent, sodium gluconate retarder and expansion agent.
[0023] In the following examples, the amounts of each component are expressed in grams (g). The amounts of each raw material are as follows: 600g of ordinary Portland cement, 200g of slag powder, 100g of fly ash, 90g of silica fume, and 10g of nano-silica; the amounts of admixtures are 3g of polycarboxylate-based high-efficiency water-reducing agent, 2g of sodium gluconate retarder, and 2g of expansive agent. The expansive agent is UEA-type low-alkali concrete expansive agent.
[0024] Example 1: In this embodiment, the water-cement ratio of the grouting material is 0.25.
[0025] Specifically, weigh out 600g of ordinary silicate cement, 200g of slag powder, 100g of fly ash, 90g of silica fume, 10g of nano silica, 3g of polycarboxylate-based high-efficiency water-reducing agent, 2g of sodium gluconate retarder, 2g of expansion agent, and 250g of water.
[0026] In preparation, ordinary silicate cement, slag powder, fly ash, silica fume, and an expanding agent are first added to a mixing container and dry-mixed at low speed for 2–3 minutes. Then, nano-silica is added, and dry-mixing continues for another 2–3 minutes to ensure uniform mixing of the powder materials. Next, a polycarboxylate-based high-efficiency water-reducing agent and sodium gluconate retarder are dissolved in 250g of water to obtain an admixture aqueous solution. Finally, the admixture aqueous solution is slowly added to the dry mix, first stirred at low speed (140±5 r / min) for 2 minutes, then stirred at high speed (285±10 r / min) for 3–5 minutes until the slurry is uniform and free of significant agglomeration, thus obtaining a mining-grade nano-modified composite cement-based grouting and reinforcement slurry with a water-cement ratio of 0.25.
[0027] Example 2: In this embodiment, the water-cement ratio of the grouting material is 0.30.
[0028] Specifically, weigh out 600g of ordinary silicate cement, 200g of slag powder, 100g of fly ash, 90g of silica fume, 10g of nano silica, 3g of polycarboxylate-based high-efficiency water-reducing agent, 2g of sodium gluconate retarder, 2g of expansion agent, and 300g of water.
[0029] The preparation method is the same as in Example 1, except that the amount of water added in this example is 300g, and a water-cement ratio of 0.30 is obtained to prepare a nano-modified composite cement-based grouting and reinforcement slurry for mining.
[0030] Example 3: In this embodiment, the water-cement ratio of the grouting material is 0.32.
[0031] Specifically, weigh out 600g of ordinary silicate cement, 200g of slag powder, 100g of fly ash, 90g of silica fume, 10g of nano silica, 3g of polycarboxylate-based high-efficiency water-reducing agent, 2g of sodium gluconate retarder, 2g of expansion agent, and 320g of water.
[0032] The preparation method is the same as in Example 1, except that the amount of water added in this example is 320g, and a water-cement ratio of 0.32 is obtained to prepare a nano-modified composite cement-based grouting and reinforcement slurry for mining.
[0033] Example 4: In this embodiment, the water-cement ratio of the grouting material is 0.35.
[0034] Specifically, weigh out 600g of ordinary silicate cement, 200g of slag powder, 100g of fly ash, 90g of silica fume, 10g of nano silica, 3g of polycarboxylate-based high-efficiency water-reducing agent, 2g of sodium gluconate retarder, 2g of expansion agent, and 350g of water.
[0035] The preparation method is the same as in Example 1, except that the amount of water added in this example is 350g, and a water-cement ratio of 0.35 is obtained to prepare a nano-modified composite cement-based grouting and reinforcement slurry for mining.
[0036] The grouts prepared in Examples 1 to 4 were subjected to tests on fluidity, setting time, bleeding rate and compressive strength, respectively, to investigate the effect of different water-cement ratios on the construction performance and mechanical properties of the mine grouting reinforcement material.
[0037] Example 5 The dosage of polycarboxylate superplasticizer is 2 g: In this embodiment, the total mass of the cementitious materials is 1000 g, including 600 g of ordinary Portland cement, 200 g of S95 grade slag powder, 100 g of secondary fly ash, 90 g of silica fume, and 10 g of nano-silica. The dosage of polycarboxylate-based high-efficiency water-reducing agent is 2 g; the dosage of sodium gluconate is 2 g; the dosage of UEA-type low-alkali concrete expansion agent is 2 g; the dosage of water is 320 g; and the water-cement ratio is 0.32. The mixing sequence, stirring process, molding method, and curing conditions of the remaining raw materials are the same as in Example 3.
[0038] Example 6: The dosage of polycarboxylate superplasticizer is 5g. In this embodiment, the total mass of the cementitious material is 1000 g, including 600 g of ordinary Portland cement, 200 g of S95 grade slag powder, 100 g of secondary fly ash, 90 g of silica fume, and 10 g of nano-silica. The dosage of polycarboxylate-based high-efficiency water-reducing agent is 5 g, sodium gluconate is 2 g, UEA-type low-alkali concrete expansion agent is 2 g, and water is 320 g, resulting in a water-cement ratio of 0.32. The mixing sequence, stirring process, molding method, and curing conditions of the remaining raw materials are the same as in Example 3.
[0039] Example 7: 300 g of slag powder: In this embodiment, the total mass of the cementitious material is 1000 g, including 500 g of ordinary silicate cement, 300 g of S95 grade slag powder, 100 g of secondary fly ash, 90 g of silica fume, and 10 g of nano-silica. Specifically, the S95 grade slag powder comprises 30 parts, and the nano-silica comprises 1 part. The amounts of polycarboxylate-based high-efficiency water-reducing agent, sodium gluconate, and UEA-type low-alkali concrete expansion agent are 3 g, 2 g, and 2 g, respectively, with 320 g of water and a water-cement ratio of 0.32. The remaining preparation methods, molding methods, and curing conditions are the same as in Example 3.
[0040] Example 8: 30 g of nano-silica: In this embodiment, the total mass of the cementitious material is 1000 g, including 580 g of ordinary silicate cement, 200 g of S95 grade slag powder, 100 g of secondary fly ash, 90 g of silica fume, and 30 g of nano-silica. The nano-silica is present in 3 parts. The remaining raw material quantities, preparation methods, molding methods, and curing conditions are the same as in Example 3.
[0041] Comparative Example 1: In step 1), the dry material used in the preparation of the slurry is all ordinary Portland cement as used in Example 1, with a water-cement ratio of 0.6, and the rest is the same as in Example 1.
[0042] Comparative Example 2: In step 1), the dry material used in the preparation of the slurry is all ordinary Portland cement as used in Example 1, with a water-cement ratio of 0.7, and the rest is the same as in Example 1.
[0043] Comparative Example 3: In step 1), the dry material used in the preparation of the slurry is all ordinary Portland cement as used in Example 1, with a water-cement ratio of 0.8, and the rest is the same as in Example 1.
[0044] Comparative Example 4: In step 1), the dry material used in the preparation of the slurry is all ordinary Portland cement as used in Example 1, with a water-cement ratio of 0.9, and the rest is the same as in Example 1.
[0045] Comparative Example 5: No nano-silica added: In this comparative example, the total mass of the cementitious materials was 1000 g, including 610 g of ordinary Portland cement, 200 g of S95 grade slag powder, 100 g of secondary fly ash, and 90 g of silica fume, without the addition of nano-silica. The dosages of polycarboxylate-based high-efficiency water-reducing agent, sodium gluconate, and UEA-type low-alkali concrete expansion agent were 3 g, 2 g, and 2 g, respectively, with 320 g of water and a water-cement ratio of 0.32. The remaining preparation methods, molding methods, and curing conditions were the same as in Example 3.
[0046] Comparative Example 6: Nano-silica doping amount: 4 parts In this comparative example, the total mass of the cementitious materials was 1000 g, including 570 g of ordinary Portland cement, 200 g of S95 grade slag powder, 100 g of secondary fly ash, 90 g of silica fume, and 40 g of nano-silica (4 parts of nano-silica). The amounts of polycarboxylate-based high-efficiency water-reducing agent, sodium gluconate, and UEA-type low-alkali concrete expansion agent were 3 g, 2 g, and 2 g, respectively. The amount of water was 320 g, and the water-cement ratio was 0.32. All other preparation methods, molding methods, and curing conditions were the same as in Example 3.
[0047] Comparative Example 7: Slag powder content: 15 parts In this comparative example, the total mass of the cementitious materials was 1000 g, including 650 g of ordinary Portland cement, 150 g of S95 grade slag powder, 100 g of secondary fly ash, 90 g of silica fume, and 10 g of nano-silica. The S95 grade slag powder was 15 parts, lower than the 20 parts limit specified in this application. The amounts of other raw materials, preparation methods, molding methods, and curing conditions were the same as in Example 3.
[0048] 1. According to the "Standard for Test Methods of Basic Performance of Building Mortar" JGJ / T70-2009, when conducting the strength test of the grout aggregate, first pour the well-stirred grout into a 70.7mm × 70.7mm × 70.7mm detachable triple standard mold, stirring evenly while pouring to ensure uniform mixing of the liquid and grout, and gently vibrate to allow air bubbles in the grout to overflow. Pour until the grout level is about 1~3 mm above the mold, then use a scraper at 45° to quickly level the grout surface. After the grout has fully set, remove the mold and test the strength at 1d, 3d, 7d and 28d respectively.
[0049] 2. Place the test block in a standard curing chamber at a temperature of (20±1)°C and a relative humidity of 95%. After curing for 24 hours, demold the test block and put it back into the curing chamber to cure for the corresponding age. Use a rigidity testing machine to test the strength of the stone body after curing for 1 day, 3 days, 7 days and 28 days at a rate of 0.002 mm / s. Test 3 test blocks for each age and take the average value as the uniaxial compressive strength of the complex at that age.
[0050] In addition, the water separation rate and fluidity of the materials were tested according to national standards such as GB / T8077-2023 "Test Method for Homogeneity of Concrete Admixtures", and the relevant test results are shown in the table.
[0051] Table 1. Performance comparison of grouting materials in the examples and comparative examples From Table 1 and Figures 3-5 It can be seen that the nano-modified composite cement-based grouting reinforcement material for mining applications of the present invention has good comprehensive performance. The flowability of the grout in each embodiment and comparative example is compared as follows: Figure 1 As shown, the initial setting time and final setting time are compared to, for example... Figure 2 As shown, the compressive strength at different ages is compared to... Figure 3 As shown. Compared with ordinary silicate cement grout, the material of this invention has higher overall fluidity and lower water separation rate, and the compressive strength at all curing ages except for the 1-day age is significantly improved, indicating that the material has good injectability, grout stability and consolidation strength, and can meet the requirements for grouting and reinforcement of fractured surrounding rock and coal and rock fissures in mines. Further comparison of Examples 1 to 4 shows that when the water-cement ratio is 0.32, the grout fluidity, stability and compressive strength at each age are more balanced. Therefore, 0.32 is taken as the preferred water-cement ratio for the material of this invention.
[0052] From Table 1 and Figure 4 It can be seen that, under the condition that the composition of the cementitious materials, the water-cement ratio, and the dosage of other admixtures remain unchanged, as the dosage of polycarboxylate-based high-efficiency water-reducing agent increases from 0.2 parts to 0.3 parts and 0.5 parts, the fluidity of the slurry increases from 21.5 cm to 28.0 cm and 30.2 cm, respectively. Specifically, when the dosage of the water-reducing agent increases from 0.2 parts to 0.3 parts, the fluidity increases by 30.2%; when it continues to increase to 0.5 parts, the fluidity increases by only 7.9%, indicating that the dispersing effect of the water-reducing agent on the cementitious particles gradually approaches saturation. Meanwhile, the initial setting time of the slurry increases from 220 min to 240 min and 280 min, and the final setting time increases from 320 min to 360 min and 390 min, respectively. When the dosage of the water-reducing agent increases to 0.5 parts, the water separation rate only increases slightly to 1.5%, and the compressive strength changes little at each age. This indicates that when the water-reducing agent dosage is 0.2 to 0.5 parts, it can improve the fluidity and workability of the slurry while maintaining good stability and consolidation strength.
[0053] From Table 1 and Figure 5It can be seen that without the addition of nano-silica, the slurry of Comparative Example 5 has a flowability of 32 cm, but the water separation rate reaches 3%, and the compressive strengths at 1 day, 3 days, 7 days, and 28 days are only 4.53 MPa, 14.00 MPa, 23.57 MPa, and 35.24 MPa, respectively. After adding 1 part of nano-silica, the water separation rate decreased to 1%, and the compressive strengths at each age increased to 5.47 MPa, 15.86 MPa, 25.16 MPa, and 37.16 MPa, respectively. When the nano-silica dosage is increased to 3 parts, the slurry flowability is 22.3 cm, the water separation rate is 0.7%, and the 28-day compressive strength still reaches 36.71 MPa, indicating that a dosage of 3 parts can still balance slurry stability, injectability, and solidified body strength. When the dosage was further increased to 4 parts, the slurry fluidity decreased to 19.4 cm, a 30.71% decrease compared to the dosage of 1 part, and the mid-to-late stage strength did not improve further. This indicates that an appropriate amount of nano-silica can improve slurry stability and solidified body strength, while excessive addition will significantly reduce slurry fluidity. Therefore, controlling the nano-silica dosage between 1 and 3 parts is more reasonable.
[0054] From Table 1 and Figure 6 It can be seen that as the content of S95 grade slag powder increased from 15 parts to 20 parts and then to 30 parts, the slurry water separation rate decreased from 1.2% to 1.0% and 0.8% respectively, while the fluidity increased from 27.2 cm to 28.0 cm and 29.1 cm, indicating that increasing the content of slag powder is beneficial to improving the fluidity and stability of the slurry. Meanwhile, the initial setting time of the slurry increased from 225 min to 240 min and 275 min, and the final setting time increased from 340 min to 360 min and 405 min. With the increase of slag powder content, the 1-day and 3-day compressive strength decreased, but the 7-day and 28-day compressive strength gradually increased. Specifically, when the slag powder content was 30 parts, the 7-day and 28-day compressive strengths reached 25.35 MPa and 37.90 MPa respectively; when the slag powder content was 15 parts, the 28-day compressive strength was only 35.90 MPa. This indicates that an admixture of 20-30 parts of slag powder can effectively balance the fluidity, stability, and mid-to-late-stage strength of the solidified body.
Claims
1. A grouting reinforcement material for mines, characterized in that, The cementitious components of the grouting reinforcement material include ordinary silicate cement, slag powder, fly ash, silica fume, and nano-silica. The slag powder comprises 20-30 parts by weight, and the nano-silica comprises 1-3 parts by weight.
2. The mine grouting reinforcement material according to claim 1, characterized in that, By weight, the ordinary silicate cement comprises 40-60 parts, fly ash comprises 10-20 parts, and silica fume comprises 5-15 parts.
3. The mine grouting reinforcement material according to claim 1, characterized in that, The slag powder is S95 grade slag powder, and the fly ash is grade II fly ash.
4. The mine grouting reinforcement material according to claim 1, characterized in that, The grouting reinforcement material also includes a polycarboxylate-based high-efficiency water-reducing agent, with the amount of the polycarboxylate-based high-efficiency water-reducing agent added being 0.2 to 0.5 parts by weight.
5. The mine grouting reinforcement material according to claim 1, characterized in that, The grouting reinforcement material also includes sodium gluconate, with the amount of sodium gluconate added being 0.1 to 0.3 parts by weight.
6. The mine grouting reinforcement material according to claim 1, characterized in that, The grouting reinforcement material also includes an expanding agent, and the amount of expanding agent added is 0.1 to 0.5 parts by weight.
7. A mine grouting reinforcement material according to claim 6, characterized in that, The expansive agent is a UEA-type low-alkali concrete expansive agent.
8. The mine grouting reinforcement material according to claim 1, characterized in that, The water-cement ratio of the grouting reinforcement material is 0.
32.
9. A method of using the mine grouting reinforcement material as described in any one of claims 1-8, characterized in that, Includes the following steps: Step 1: Add ordinary silicate cement, slag powder, fly ash, silica fume and expansion agent to a mixing container and dry mix for 2-3 minutes; then add nano silica and continue to dry mix for 2-3 minutes to obtain a mixed dry powder. Step 2: Add polycarboxylate superplasticizer and sodium gluconate to water and stir until fully dissolved to obtain an aqueous solution of the additive; Step 3: Slowly add the aqueous solution of the additive to the mixed dry powder and stir until the slurry is uniform and there is no obvious agglomeration, thus obtaining the mine grouting reinforcement slurry.
Citation Information
Patent Citations
Preparation method and device of Anshan basalt stratum grouting material
CN121850502A